Study of Reinforced Concrete Beams on Yielding Supports under Short-Term Dynamic Loading - Z. R. Galyautdinov (Железобетонные конструкции)
Civil defense structures are exposed to short-term dynamic loads of high intensity. In order to reduce dynamic forces and movements of structures, active methods of protection, which include yielding supports, have been increasingly used in recent years. In this paper, the assessment of the influence of the yielding of supports is carried out based on the results of the calculation of reinforced concrete beams on yielding supports under short-term dynamic loading. The work of the structure is considered in the conditionally elastic stage, and yielding supports in the elastic, plastic and hardening stages. Collapsible inserts of an annular profile are accepted as yielding supports. For reinforced concrete beams on yielding supports, the equation of motion, function and coefficient of dynamism are determined. It has been established that the use of elastic yielding supports can have both positive and negative effects on the operation of structures, which is expressed in the excess of forces and displacements of structures on elastic supports relative to elements on non-displaceable supports. When yielding supports are deformed in the elastic and plastic stages, there is a sharp decrease in the dynamic coefficient of beams, and, consequently, stresses and deformations in structures. The transition of yielding supports to the stage of hardening leads to a sharp increase in the dynamic coefficient of the structure.